A Study on Factors Influencing Customers to Prefer the Policies of Life Insurance of India in Palakkad District - Praseeja P; Dr. N.Shanmughavadivu (International Journal of Engineering and Management Research, 2018)
The policyholders once when they become a part of the LIC feel free about the safety of their wards since it takes care of fixed financial benefits based on the premium and the type of the policy the opted for . The families of the non-policyholders meet out uncertainty in many cases. So, there is an attraction towards life insurance and concern and awareness about the industry is also improving. People who care much about them and their families hold life insurance. The tastes and preferences of policyholders not the same. The LIC of India has been introducing variety of policies based on the preferences of the policyholders. It is observed that many policyholders have taken more than one policy based on their job nature and family members interest. It is a clear indication that they are very much interested in utilizing maximum benefits from Insurance companies. Some people give due importance to money value and high returns on their investments. But greater risks are inherent advantages expected from LIC products. The present study emphasis the factors influencing customers to prefer the policies of life insurance of India in Palakkad District.